Modeling and simulation of HVDC transmission - Han, Minxiao; Gole, Aniruddha (IET energy engineering series ;, 2020)
This book contains 12 chapters that discusses the following topics: HVDC and the needs for modeling and simulation; General practices of HVDC modeling and simulation; Electromagnetic modeling of LCC-HVDC; VSC system modeling and stability analysis; Electromagnetic modeling of DC grid; Electromagnetic simulation of HVDC transmission; Electromechanical transient simulation of LCC HVDC; Electromechanical transient simulation of VSC HVDC; Dynamic phasor modeling of HVDC systems; Small-signal modeling of HVDC systems; Hybrid simulation for HVDC and Real-time modeling and simulation for HVDC systems.